UTILIZING QUILLBOT PARAPHRASER TO MINIMIZE PLAGIARISM IN STUDENTS' SCIENTIFIC WRITING - Lisa Rakhmanina,Reko Serasi (Novateur Publications, 2022)
Writing is obviously important because it is used to communicate with people all around the  world. However, its significance cannot be separated from the fact that writing is one of the most difficult components of language competency. Moreover, the issue of plagiarism in writing remains a trending topic, as its existence is harmful to a writer whose work is copied without proper citation. In this instance, both lecturers and researchers identify instances of plagiarism in student writing (Choi, 2012). Some people, especially internet-based people, are careless with their copy-paste work.
Keywords: Quillbot; student writing